2023
DOI: 10.1007/s11356-023-25447-1
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater vulnerability to pollution assessment: an application of geospatial techniques and integrated IRN-DEMATEL-ANP decision model

Abstract: This study evaluated the susceptibility to groundwater pollution using a modified DRASTIC model. A novel hybrid multi-criteria decision-making (MCDM) model integrating Interval Rough Numbers (IRN), Decision Making Trial and Evaluation Laboratory (DEMATEL), and Analytical Network Process (ANP) was used to investigate the interrelationships between critical hydrogeologic factors (and determine their relative weights) via a novel vulnerability index based on the DRASTIC model. The flexibility of GIS in handling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…According to Haied et al (2021), many studies have shown the importance of the correlation between natural and/or anthropogenic pollution and the vulnerability model. Recently, some models have been used in order to assess the groundwater vulnerability to pollution, such as the DRASTIC model (Chukwuma et al, 2023; Haied et al, 2021; Liang et al, 2016). Previous works, which are related to the Mahdia‐Ksour Essef aquifer study, used the DRASTIC model (Nasri et al, 2021; Saidi, 2011) in order to investigate the groundwater vulnerability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Haied et al (2021), many studies have shown the importance of the correlation between natural and/or anthropogenic pollution and the vulnerability model. Recently, some models have been used in order to assess the groundwater vulnerability to pollution, such as the DRASTIC model (Chukwuma et al, 2023; Haied et al, 2021; Liang et al, 2016). Previous works, which are related to the Mahdia‐Ksour Essef aquifer study, used the DRASTIC model (Nasri et al, 2021; Saidi, 2011) in order to investigate the groundwater vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…According to Chukwuma et al (2023), the groundwater resources is important to all life forms, whether for human beings, animals or plants. Their importance is mainly manifested by their use as valuable water resources especially for drinking purposes (Narsimha & Wu, 2019) and for livestock farming and irrigation purposes (Skevas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Geomorphometric properties [Ghasemlounia and Utlu, 2021]. For this purpose, several methods have been used, such as Morphometric analysis (MA) approach [Meshram et al, 2022 [Yariyan et al, 2020;Chukwuma et al, 2023], are utilized as techniques to identify areas with a high potential for producing floods. This study suggests using a hydrological study approach for Oued Martil and its tributaries, ranging from Oued Khémis to the river mouth, in response to the challenges associated with flood mapping in the study area.…”
Section: Introductionmentioning
confidence: 99%